Impacts of root pruning intensity and direction on the phytoremediation of moderately Cd-polluted soil by Celosia argentea. Issue 11 (19th September 2022) - Tang, Youjun; Gan, Tian; Cao, Min; Song, Jinnuo; Chen, Dan; Luo, Jie
Abstract: Root pruning can impact the physiological functions of various plants, which influence phytoremediation. A series of root pruning treatments with different combinations of direction (two-side pruning and four-side pruning) and intensity (10, 25, and 33% pruning) were performed on Celosia argentea L. All two-side pruning treatments, regardless of intensity, decreased the dry biomass of the C. argentea roots at the end of the experiment relative to that of the control. However, the two-side-10% and two-side-25% pruning treatments stimulated the growth rate of the plant leaves significantly by 58.6 and 41.4%, respectively, relative to that of the control, and even offset the weight loss of the plant roots. Contrastingly, the two-side-33% pruning treatment reduced the biomass yield of leaves by 24.1%. For the four-side pruning treatments, the low intensity increased the dry weight of both the plant roots and leaves, while both decreased under high-intensity root pruning. The dry weight, Cd content, pigment level, and photosynthetic efficiency in the four-side-10% treatment were higher than those in the other treatments during the experiment. This study indicates that root pruning with a suitable combination of direction and intensity can positively influence the Cd removal ability of C. argentea . Novelty statement: Our study suggests that a suitable root pruning pattern can significantly increase the phytoremediation effect of Celosia argentea L. Compared with chemical and biological regulation including plant hormone application, chemical reagent spraying, and endophytes inoculation which might introduce unpredictable risks into the ecological system, root pruning can be considered as an environmentally friendly physical trigger to modulate physiological features and to induce advantages in plants. This finding can be extrapolated into the real-world easily since root pruning is an established, convenient, and feasible method. We believe readers would be interested in this method.